Functional outcome of patients undergoing lumbar discectomy - Singh, Harpreet; Bhavsar, Parth B.; Singh, Ankit; Patel, Saurin (International Journal of Research in Orthopaedics, 2018)
Background: Sciatica resulting from a lumbar intervertebral disc herniation is the most common cause of radicular leg pain in adult working population. It can be treated with both conservative and operative methods. In our study, surgical treatment of lumbar disc prolapse has been done by open discectomy. We wish to assess the outcome of surgery in patients with lumbar disc prolapse undergoing lumbar discectomy. Methods: 40 patients were included in this study and were followed up for up to 1 year postoperatively. We assessed the outcome of each patient with ODI and VAS post-operatively and on follow-up at 3 weeks, 6 months and 1 year. Subjective evaluation of the patient’s satisfaction at the final follow-up was also done. Results: We found that males had higher incidence of PIVD with an average duration of symptoms before surgery about 8.62 months. Left side was most involved and level l4-l5 was most involved level. The mean ODI and VAS score pre-operatively were 26.85±4.20 and 7.73±0.88 respectively, which changed to 4.48±5.15 and 1.70±1.57, respectively at 1 year post-operative follow-up. These were statistically highly significant. Most of the patients (34) gave a subjective evaluation as excellent at 1 year follow-up. Conclusions: Our study established that open discectomy has a satisfactory functional outcome and leads to a significant improvement in the patients’ quality of life.